Diagnostic Performance of Routine Brain MRI Sequences for Dural Venous Sinus Thrombosis - Patel, D.; Machnowska, M.; Symons, S.; Yeung, R.; Fox, A.J.; Aviv, R.I.; Jabehdar Maralani, P. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: Signs suggestive of unexpected dural venous sinus thrombosis are detectable on routine MR imaging studies without MRV. We assessed performance characteristics and interrater reliability of routine MR imaging for the diagnosis of dural venous sinus thrombosis, focusing on the superior sagittal, transverse, and sigmoid sinuses.MATERIALS AND METHODS: This case series included 350 patients with MRIs performed with contrast-enhanced MRV and 79 patients with routine MRIs performed within 48 hours of a CTV from 2008 to 2014 (total, n = 429). Routine MR images were separated from the contrast-enhanced MRVs and CTVs. Three neuroradiologists, blinded to clinical data, independently reviewed the MRIs for signs of dural venous sinus thrombosis, including high signal on sagittal T1, loss of flow void on axial T2, high signal on FLAIR, high signal on DWI, increased susceptibility effects on T2*-weighted gradient recalled-echo imaging, and filling defects on axial contrast-enhanced spin-echo T1WI and/or volumetric gradient-echo T1WI. Two neuroradiologists independently reviewed contrast-enhanced MRVs and CTVs to determine the consensus gold standard. Interrater reliability was calculated by using the κ coefficient.RESULTS: Contrast-enhanced MRV and CTV confirmed that dural venous sinus thrombosis was present in 72 of 429 cases (16.8%). The combination of routine MR sequences had an overall sensitivity of 79.2%, specificity of 89.9%, and moderate interrater reliability (κ = 0.50). The 3 readers did not have similar performance characteristics. 69.4% of positive cases had clinical suspicion of dural venous sinus thrombosis indicated on imaging requisition.CONCLUSIONS: Routine MR images can suggest dural venous sinus thrombosis with high specificity in high-risk patients, even in cases without clinical suspicion.CE-3D-T1WIvolumetric contrast-enhanced GRE T1-weighted imagingCEMRVcontrast-enhanced MRVCE-SE-T1WIcontrast-enhanced spin-echo T1-weighted imagingDVSTdural venous sinus thrombosisGRET2*-weighted gradient recalled-echo imaging